(untitled) (Revista de Artes Marciales Asiáticas, 2012)
The objective of this article is to give a short overview of different types of a product called “Persian watered steel” and show its beauty through examples of edged weaponry. I use the terms “watered steel,” “Damascus steel,” and “crucible steel” interchangeably throughout this article, and those terms are also explained. Watered steel is produced from steel made in crucibles, and the resulting differences in properties occurring during the process will be explained. The resulting quality is vital in producing edged weapons that are of praiseworthy significance. Another section of this article deals with the production centers of crucible steel and gives a short overview of this topic, including a discussion on watered steel in historical accounts. Lastly, the classification of properties of watered steel in early modern times is discussed.